Why does Translation Matter? Fissures in English Translation of Pārijāta’s Śirīṣakō Phūla - Phuyal, Komal Prasad (Nepal Journal of Multidisciplinary Research, 2025)
Background: The relevance of translation is widely questioned in applied linguistics. The linguists attempt to answer the question: why does translation matter? The question is more pertinent today, as the network society has revealed an entirely novel facet in the age of artificial intelligence. Methods: This study draws on Tejeswani Niranjana and Gayatri Chakravorty Spivak's theoretical discussions on the functioning of power in the study of translation to interpret Pārijāta’s Śirīṣakō Phūla (1964) in its translation by Tanka Vilash Varya as Blue Mimosa (1972). This study reveals that the target text follows the twists and turns of the source text's message from the text's title onward. Conclusion: Conventionally, translation allows linguists to travel between the source and the target language, preserving the message of the source and conveying it in the target. However, a host of factors play a critical role in conveying the message in the target text. Often, power emerges covertly to modify the text's meaning. Novelty: This paper argues that the target text in English fails to convey the meaning of Pārijāta's text, Śirīṣakō Phūla, due to the play of power in translation.